Green biosynthetic silver nanoparticles from Ageratum conyzoides as multifunctional hemostatic agents: Combining hemostasis, antibacterial, and anti-inflammatory properties for effective wound healing - Yang Li; Yinfeng Tan; Huange Zhao; Shiting Chen; Azadeh Nilghaz; Rong Cao; Songlin Zhou (Materials Today Bio)
Widespread interest in new hemostatic agents arises from the challenge of simultaneously satisfying the requirements of hemostatic, antibacterial, and anti-inflammatory properties while also considering the associated economic costs. An ideal hemostasis material should facilitate rapid hemostasis, intervene against infection, promote wound healing, and be cost-effective and easy to prepare. Herein, we demonstrate that medicinal plant-derived silver nanoparticles (AgNPs) exhibit the potential to constitute a promising multifunctional hemostatic reagent library. Biogenic synthesis of AgNPs utilizing Ageratum conyzoides extracts, referred to as AC-AgNPs, successfully combines the hemostatic and anti-inflammatory properties of Ageratum conyzoides with the inherent antibacterial activity exhibited by AgNPs. In-vitro coagulation experiments indicate that AC-AgNPs have a strong hemostatic effect, which is related to their size, concentration, and negative charge, and they exhibit low cytotoxicity and hemolysis. Subsequent experiments including scanning electron microscopy, flow cytometry, western blotting, and network pharmacology analysis have revealed that AC-AgNPs can cause platelet activation and aggregation, stimulated kallikrein-kinin system, shorten activated partial thromboplastin and prothrombin time, and increase fibrinogen content. These findings indicate that AC-AgNPs act on multiple signaling pathways, including endogenous and exogenous coagulation pathways, complement system, platelet activation, and aggregation. Furthermore, the hemostatic efficacy of AC-AgNPs is demonstrated in mouse models of tail amputation and liver injury, where AC-AgNPs significantly reduce the amount of blood loss and the bleeding time. Our work shows that AC-AgNPs possess strong hemostatic, anti-inflammatory, and antibacterial capabilities, ultimately facilitating wound healing. The biogenic synthesis of AgNPs from medicinal plants could be a multifunctional hemostatic candidate for practical application.